Mengajak Masyarakat Ikut Aktif dalam Kampanye Friendly Bandung Melalui Instalasi Interaktif - Melita Setiawan; Alfonzo R. Kopaha (Wimba : Jurnal Komunikasi Visual, 2015)
Friendly Bandung is an international city branding campaign which developed within different aspect and promoted by creative community in Bandung city. This campaign was initiated because the government's facility has not used effectively by many of pedestrian yet. The increased use of crossing bridge was one alternative way to support the convenience for both pedestrian and the rest of road users. Interactive installation has a potency to persuade pedestrian in using crossing government facilitation as it fits the open minded and friendly characters of Bandung's people. This study collected data through literature study, observation and interview. Moreover, this study also connected the phenomena with several theories such as fun theory and the concept of interaction. The interactive installation could become a pioneer of the safety, security and smooth traffic flow by persuade pedestrian to use crossing bridge.